Can Pediatric Orthopaedic Surgery be Done Safely in a Freestanding Ambulatory Surgery Center? Review of 3780 Cases. Issue 1 (January 2021) - Sheffer, Benjamin W.; Kelly, Derek M.; Spence, David D.; Walker, Kent L.; Westbrooks, Timothy J.; Palm, Preston H.; Nolan, Vikki G.; Sawyer, Jeffrey R.
Abstract : Background: The purpose of this study was to determine the intraoperative and 30-day postoperative complication rates in a large consecutive cohort of pediatric patients who had orthopaedic surgery at a freestanding ambulatory surgery center (ASC). The authors also wanted to identify the rates of same-day, urgent hospital transfers, and 30-day hospital admissions. The authors hypothesized that pediatric orthopaedic procedures at a freestanding ASC can be done safely with a low rate of complications. Methods: A retrospective review identified patients aged 17 years or younger who had surgery at a freestanding ASC over a 9-year period. Adverse outcomes were divided into intraoperative complications, postoperative complications, need for the secondary procedure, unexpected hospital admission on the same day of the procedure, and unexpected hospital admission within 30 days of the index procedure. Complications were graded as grade 1, the complication could be treated without additional surgery or hospitalization; grade 2, the complication resulted in an unplanned return to the operating room (OR) or hospital admission; or grade 3, the complication resulted in an unplanned return to the OR or hospitalization with a change in the overall treatment plan. Results: Adequate follow-up was available for 3780 (86.1%) surgical procedures. Overall, there were 9 (0.24%) intraoperative complications, 2 (0.08%) urgent hospital transfers, 114 (3%) complications, and 16 (0.42%) readmissions. Seven of the 9 intraoperative complications resolved before leaving the OR, and 2 required return to the OR. Neither complications nor hospitalizations correlated with age, race, gender, or length or type of surgery. There was no correlation between the presence of medical comorbidities, body mass index, or American Society of Anesthesiologists score and complication or hospitalization. Conclusions: Pediatric orthopaedic surgical procedures can be performed safely in an ASC because of multiple factors that include dedicated surgical teams, single-purpose ORs, and strict preoperative screening criteria. The rates of an emergency hospital transfer, surgical complications, and 30-day readmission, even by stringent criteria, are lower than those reported for outpatient procedures performed in the hospital setting. Level of Evidence: Level IV—case series. Abstract : Supplemental Digital Content is available in the text.